Traversing the topsy-turvy terrains: The coconut sector in Kingdom of Tonga - Kulufeinga ‘Anisi Bloomfield, Jayasekhar Somasekharan, Tevita Lautaha,; Maile Tahafitu Fa’ase’e, ‘Ilaisaane ‘OliviaTu’ itupou (Journal of Plantation Crops, 2017)
Coconuts are inextricably linked to the culture, tradition and economy of Tonga from time immemorial. Although coconut sector enjoyed a predominant position in the national economy until the late 1980s, thereafter the sector has experienced a downfall. The 1990s and 2000s witnessed a stagnant coconut economy in Tonga and in the recent times, the role played by the sector has become insignificant. The comparative position of Tonga with respect to the major Pacific islands, in terms of production, trade and competitiveness is not advantageous to the country. The contribution of coconut sector in the national economy and export earnings has been dwindling in recent years. It was also seen that the export diversification in products and markets are absent. There are only a few exporters operating in the sector, therefore the benefit of perfect competition and economy of scale is not realized. In contrast, the coconut sector in Tonga still has the potential to provide year round income to the farmers. Therefore, the sector needs an adequate impetus in all the nodes from production to the exports, with plausible options and strategies to make it sustainable.